Grandchild care and life satisfaction of older adults: Empirical evidence from China - Dong, Xiangyu; Ling, Hongxiang; Yang, Tianyi; Wang, Kun (Frontiers in Psychology, 2023)
Background In China, grandchild care plays an important social role later in life. The effects of grandchild care on physical health and depression in older adults have been illustrated. However, there is a gap in research on grandchild care and life satisfaction of older adults specifically based on the Chinese experience. Method Based on 7,079 individuals’ data from 2018 China Longitudinal Aging Social Survey (CLASS), this study explored the impact of grandchild care on older adults’ life satisfaction by using Ordinary Least Squares (OLS), Propensity Score Matching (PSM), and instrumental variables (IV) models. Results The empirical results indicated that (1) life satisfaction was significantly higher for older adults who undertook grandchild care compared to those who did not; (2) non-coresiding grandparents showed higher life satisfaction than those non-carers, and this effect was not found in custodial grandparents or three-generation household grandparents; (3) higher life satisfaction of grandchild caregivers was achieved through reduced loneliness, enhanced self-efficacy, and increased emotional support from children, with the latter being the greatest contribution; and (4) the improving effect of grandchild care on life satisfaction was found mainly in the group of older adults who were male and in rural households. Conclusion There was a significant difference in life satisfaction between older Chinese adults who provided grandchild care and those who did not. Efforts in terms of old age policy protection and family relationships should be made to enhance the subjective well-being of older adults.